2015
DOI: 10.3390/ijerph120100521
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Malawian Mothers’ Malaria Knowledge, Healthcare Preferences and Timeliness of Seeking Fever Treatments for Children Under Five

Abstract: Malaria is one of the major public health problems in Malawi, contributing to the majority of morbidity and mortality among children under five. Ignorance of malaria symptoms results in delayed treatment, which often degenerates into fatal emergencies. This study analyzed the impact of maternal malaria knowledge on healthcare preferences and timeliness of treating children with reported fever. The Malaria Indicator Survey data for 2012, which were adequately weighted, were analyzed using multinomial logit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
5
25
2
Order By: Relevance
“…This by implication indicates that households' that answered yes to the question of whether they use private hospital when sick had significantly higher probability of having good health when compared with their counterparts who answered no. This is in line with previous finding such as Oyekale (2015) who opined that many poor households seek free malaria treatment from public hospitals, but that should not be at the detriment of quality and efficiency. That by implication indicates that private hospitals are known to always deliver quality service than their public counterpart and this could be the reason why it enhances the respondents' health status.…”
Section: Logistic Regression Analysis Results Of Socioeconomic and Envsupporting
confidence: 92%
“…This by implication indicates that households' that answered yes to the question of whether they use private hospital when sick had significantly higher probability of having good health when compared with their counterparts who answered no. This is in line with previous finding such as Oyekale (2015) who opined that many poor households seek free malaria treatment from public hospitals, but that should not be at the detriment of quality and efficiency. That by implication indicates that private hospitals are known to always deliver quality service than their public counterpart and this could be the reason why it enhances the respondents' health status.…”
Section: Logistic Regression Analysis Results Of Socioeconomic and Envsupporting
confidence: 92%
“…1 Previous investigations into treatment-seeking in Malawi, and other malaria-endemic nations, tended to focus solely on children younger than 5 years. 6,[20][21][22][23][24] We studied treatmentseeking among people of all ages from several different transmission settings in Malawi, and these data support the findings from several other analyses: school-age children are likely important P. falciparum transmission reservoirs in this area. We previously found that SAC have the highest prevalence of P. falciparum infections, 9 the highest prevalence of gametocytes, 25 and are the least likely to sleep under ITNs.…”
Section: Discussionsupporting
confidence: 61%
“…Early treatment of childhood malaria depends upon mothers’ perception about malaria and prompt recognition of signs and symptoms of the disease and treatment-seeking behaviour [10, 11]. Studies have reported poor practice of health seeking among caregivers of under five children mainly due to caregivers not recognizing signs of childhood illness for seeking care immediately for common childhood illnesses including fever [12].…”
Section: Introductionmentioning
confidence: 99%